Quality Changes of Salt-Smoke-Dried Tengra (Mystus tengara) during Storage at Room Temperature (28 To 32°C) in Different Packs - Hossain, MI; Shikha, FH; Murad, MMH (Journal of Environmental Science and Natural Resources, 2021)
Packing has effect on the quality parameters of a food product. Here, studies were conducted to produce premium quality salt-smoke-dried tengra fish (Mystus tengra) by combining the effect of salt and smoke in a smoking kiln. During the study, moisture content in tengra fish fell from an initial value of 77.17% to a range of 18.56% to 29.09%, protein content from 51.36% to a range of 40.54% to 51.36%, lipid content from 16.20% to a range of 6.50% to 16.20% and ash content from 13.40% to a range of 8.17% to 13.40% for salt-smoke-dried products at the end of the storage period. On the other hand, the TVB-N value of fresh fish muscle was obtained 2.90 (mg/100g), pH 6.80 and bacterial load 1.13×104 (CFU/g), with the progress of storage period 180 days which values increased to the range of 28.16 to 29.34 mg/100g, 6.27 to 7.86 and 4.42 ×105to 6.82 x 105CFU/g, respectively. From the obtained results this study could be concluded that- if tengra is salted, smoked and dried properly can be stored at room temperature (26 to 28°C) for about 6 months without major deterioration of the fish and among three packs vacuum pack might be better option for storing salt-smoke-dried tengra. Environ. Sci. & Natural Resources, 12(1&2): 191-197, 2019